(untitled) (Journal of NELTA, 2018)
The article analyses novice teachers’ perception on the pre-service teacher education courses of English at Tribhuvan University (TU) and to describe their beliefs and satisfaction on teaching profession. It also aims to describe novice teachers’ practice to implement the acquired knowledge and skills of these courses in their teaching field. Narrative inquiry was adopted as a research method and three novice teachers of community school of Sindhuli were selected as informants following purposive sampling technique. The semi-structured interview was used in order to elicit in depth data from the participants. Content analysis framework was used to analyse data by developing main themes into codes and using them to look for relevant features in the text. The findings divulge that pre-service teacher education courses are supportive and satisfactory for novice teachers as it provides methodological skill and theoretical knowledge to them to teach in the classroom. The novice teachers, who strongly believe in the teaching profession, also think that the contents are theoretically appropriate but they lack some practical applications.